The Effectiveness of the Contribution of LBM Dayah MUDI Mesjid Raya among the Samalanga Community - Luthfi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
The aims of this study is to find out The Effectiveness of the Contribution of LBM Dayah MUDI Mesjid Raya among the Samalanga Community. This study used qualitative method. The result of this study shows The presence of Dayah MUDI LBM Samalanga Great Mosque of Samalanga has provided significant effectiveness in the community and even various unresolved problems have been able to be properly resolved by the Samalanga MUDI Dayah LBM. The perceived results of LBM can easily be accessed by the public via the internet, either Youtube, Facebook and the like, in addition to using radio media and da'wah bil kalam (writing) with the presence of a collection of LBM MUDI books at the Samalanga Grand Mosque. Even Umara also really appreciates the steps and contributions of LBM for the people of Samalanga, especially Aceh and outside Aceh in general.